2023
DOI: 10.1371/journal.pone.0286865
|View full text |Cite
|
Sign up to set email alerts
|

Altered GC- and AT-biased genotypes of Ophiocordyceps sinensis in the stromal fertile portions and ascospores of natural Cordyceps sinensis

Abstract: Objective To examine multiple genotypes of Ophiocordyceps sinensis in a semi-quantitative manner in the stromal fertile portion (SFP) densely covered with numerous ascocarps and ascospores of natural Cordyceps sinensis and to outline the dynamic alterations of the coexisting O. sinensis genotypes in different developmental phases. Methods Mature Cordyceps sinensis specimens were harvested and continuously cultivated in our laboratory (altitude 2,254 m). The SFPs (with ascocarps) and fully and semi-ejected as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 39 publications
(342 reference statements)
1
35
0
Order By: Relevance
“…Genotypes #4 and #15 of the AT-biased Cluster B of O. sinensis ( cf . Figure 2) were reported to exist in the stroma and stromal fertile portion (densely covered with numerous ascocarps) of natural C. sinensis but not in the ascospores (Li et al . 2023b, 2023c), consistent with the failure to identify Genotype #4 of AT-biased Cluster B in mono-ascospores as reported by Li et al .…”
Section: The Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Genotypes #4 and #15 of the AT-biased Cluster B of O. sinensis ( cf . Figure 2) were reported to exist in the stroma and stromal fertile portion (densely covered with numerous ascocarps) of natural C. sinensis but not in the ascospores (Li et al . 2023b, 2023c), consistent with the failure to identify Genotype #4 of AT-biased Cluster B in mono-ascospores as reported by Li et al .…”
Section: The Resultsmentioning
confidence: 99%
“…, Natural C. sinensis ) collected from an alpine meadow of Nyingchi, Tibet Autonomous Region, China, but not the 3 pure GC-biased Genotype #1 H. sinensis strains reported by Wei et al . (2016), Li et al . (2023b, 2023c) reported that the fully ejected ascospores of natural C. sinensis contained GC-biased Genotypes #1 and #14, AT-biased O. sinensis Genotypes #5–6 and #16 within AT-biased Cluster A ( cf .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations